STUDY OF METABOLIC SYNDROME IN INDIAN POPULATION WITH COMPARISON OF TWO DEFINITIONS - Rajwal, Neha; Singh, Jasjot; Neupane, Nurakant (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Metabolic syndrome (MetS) is described as the collection of risk factors for cardiovascular disease such as hypertension, hyperglycemia/ insulin resistance, abdominal obesity, and dyslipidemia. In developed countries, MetS is highly prevalent among adults and is an emerging health problem in developing countries. In this study, we used the International Diabetes Federation (IDF) and National Cholesterol Education Program- Adult Treatment Panel-III (NCEP-ATP III) to define the Mets. The aim of this research was to evaluate the prevalence of MetS, its components, and its major risk factors among adults ≥20 in Jammu and Kashmir according to IDF and the NCEP ATP III criteria. Methods: The project was conducted in the Department of Biochemistry, Laboratory Medicine, Shri Mata Vaishno Devi Narayana Superspeciality Hospital, Katra, and Jammu and Kashmir in 100 subjects between the age groups of 20 and 80 years old attending the OPD from 2 January to 30 April 2017. Results: MetS was diagnosed in 57% and 55%, gender-wise distribution came out to be 45.6% and 52.7% in men, and in women, we found 54.3% and 47.3%, according to IDF and the NCEP ATP III definition, respectively. Conclusion: In our study, IDF criteria were better for the early diagnosis of MetS. On the basis of gender prevalence in all parameters in IDF, females are at risk, and in NCEP ATP III, males are more at risk. According to the IDF, central obesity is the only the risk for women.